Occupational Labor Shortages : Concepts, Causes, Consequences, and Cures - Barnow, Burt S. (Book collections on Project MUSE., 2013)
"Barnow, Trutko, and Piatak focus on whether persistent occupation-specific labor shortages might lead to inefficiencies in the U.S. economy. They describe why shortages arise, the difficulty in ascertaining that a shortage is present, and how to assess strategies to alleviate the shortage. Four occupations are used as test cases: 1) special education teachers, 2) pharmacists, 3) physical therapists, and 4) home health and personal care aides. For each of these occupations the authors summarize evidence that reveals whether it is currently or has recently experienced a labor shortage and suggest possible ways to alleviate the shortage if it is present. The authors close with a chapter discussing their conclusions and potential uses for occupational shortage data, including in helping determine immigration policy. They also discuss the limited nature of the occupational data currently collected by the Bureau of Labor Statistics and how the federal and state governments could expand their data collection efforts to assist policy formation."--Publisher's website